Reviewing continuing professional development concept of English teachers from the lens of Diffusion of Innovation Theory - Ahmad Jawahir (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2021)
The main problem of the recent study is how the concept of English teacher Continuing Professional Development is reviewed from Everett Rogers’ Innovation Diffusion Theory. So, the research aimed at finding the review of the Innovation Diffusion Theory of Rogers toward the concept of Continuing Professional Development of English teachers in Indonesia. This study employed library research as the method and the researcher himself as the instrument to collect data deriving from books as a primer resource and ministry regulation and journal articles as secondary resources. It was conducted through several stages ranging from selecting topics based on the problem; exploring information related to the topic; determining research focus; reading the books, regulations and articles as data resources; recording what was found as research data; and, processing the recorded data. Data were analyzed through induction and interpretation. The result showed that teacher continuing professional development is an implementation of innovation diffusion. It forms a cycle or an endless chain, in which, firstly, innovative work is invented and adopted by innovative teachers; next, it is reported, reflected and published in the form of scientific book, paper or article; then, the scientific work is presented in functional or technical education and training or teacher collective activity as a channel of communication with early adopter teachers; and, the adopter teachers are inspired to make another innovation. Keywords: Continuing Professional Development; Innovation Diffusion Theory; English teachers